Measurement of a 5:1 blood pump model - Soh, Boon Chuan (2016)
Mechanical Circulatory System was developed to provide cardiovascular disease patients with heart transplant alternative. The Kyoto University Magnetically Suspended Centrifugal Blood Pump uses magnetically suspended impeller to eliminate the use of bearing and seal, thus reducing heat generation, leakage and contamination of blood. However, hemolysis and thrombus formation in the 0.2 mm clearance gap between the impeller surface and the pump casing is of primary concern. An enlarged model using of five times was built by applying dimensional analysis and the pump similarity law to study the fluid flow behavior within the clearance gap. Hot wire anemometry was used to measure the tangential and radial velocity at 3 axial planes (z/d = 0.25, 0.5 and 0.75). A total of 504 readings (7 radial x 72 angular) were taken at each axial plane. The tangential, radial, resultant, flow angle and vector plots were presented in this report. The results obtained show flow magnitude is higher and flow in a more tangentially manner at the outer radial position and at the higher axial position. No recirculation was observed and washout effect was more dominant in the region near the splitter plate. These suggest that hemolysis and thrombus formations are minimal hence the pump is a compactable bio-centrifugal blood pump. The experimental data would be useful for future analysis and in developing an optimum blood pump design.